2007
DOI: 10.2165/00126839-200708060-00006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Piperine on the Pharmacokinetics of Nevirapine under Fasting Conditions

Abstract: This pilot study provided evidence for enhanced bioavailability of nevirapine when administered with piperine. Further in-depth studies in a large number of patients receiving different dosage regimens are required to confirm these results and further our understanding of a possible clinical advantage arising from the bioenhancement capabilities of piperine in the treatment of HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 14 publications
1
29
0
1
Order By: Relevance
“…Blood samples were collected post-dose. The results of the study showed that there was an enhanced bioavailability of nevirapine when administered with piperine [123] .…”
Section: Recent Advances Of Bioenhancersmentioning
confidence: 95%
“…Blood samples were collected post-dose. The results of the study showed that there was an enhanced bioavailability of nevirapine when administered with piperine [123] .…”
Section: Recent Advances Of Bioenhancersmentioning
confidence: 95%
“…Additionally, the in vitro absorption rate of piperine is relatively high compared with other natural products like curcumin without any metabolic modification of piperine during the absorption process [393]. Piperine is widely used as a bioavailability enhancer for a diverse group of therapeutic agents including the antimicrobial agent rifampicin [394], nevirapine which is a potent inhibitor of human immunodeficiency virus (HIV)-1 reverse transcriptase [395] and curcumin which has anticancer properties [396]. Piperine has various biological effects including antioxidant activity [397] anti-inflammatory effect by inhibiting PMA-induced COX-2 [398].…”
Section: Approachesmentioning
confidence: 99%
“…It also contains small amounts of safrole (C 10 H 10 O 2 ), pinene (C 10 H 16 ), sabinene (C 10 H 16 ), limonene (C 10 H 16 ), caryophyllene (C 15 H 24 ) and Linalool (C 10 H 18 O) compound. The fruits have variety of activities including CNS depressant, antipyretic, analgesic, hepatoprotective (Lee et al 1984), bioavailability enhancer Kasibhatta and Naidu 2007), antioxidant (Khajuria et al 1997) and anti-inflammatory (Majumdar et al 1990). …”
Section: Introductionmentioning
confidence: 99%